Advances in Nanocellulose-Based Composites for Sustainable Food Packaging - Baoying Shi; Di Wu; Yu Lin; Xinyu Xu; Siqi Xie; Guiyuan Zhao; Yufeng Wang (BioResources, 2025)
Nanocellulose, a sustainable and versatile nanomaterial derived from abundant natural resources such as plants and bacteria, has emerged as a promising candidate for advancing eco-friendly food packaging. This review summarizes recent advancements in nanocellulose composites, focusing on their preparation methods, enhanced mechanical and barrier properties, applications in food preservation, safety profiles, and biodegradability. Nanocellulose composites, synthesized via techniques such as solution casting, melt intercalation, layer-by-layer self-assembly, in situ polymerization, coating, and ring-opening polymerization, can exhibit exceptional mechanical strength, oxygen and moisture barrier performance, as well as compatibility with active agents such as antioxidants and antimicrobials. Studies highlight the role of nanocellulose in reducing polymer composite permeability while maintaining biodegradability. Despite these advantages, challenges such as high production costs, energy-intensive methods (e.g., sulfuric acid hydrolysis), and hydrophilic limitations hinder industrial scalability. Emerging strategies, including enzymatic processing and surface modifications (acetylation, oxidation), offer pathways to enhance hydrophobicity, dispersion, and thermal stability. Future research should prioritize scalable, low-cost production technologies and expanded applications in smart and active packaging systems. By addressing these challenges, nanocellulose composites hold significant potential to revolutionize sustainable packaging, aligning with global demands for reduced environmental impact and enhanced food security.